An Intelligent FPGA Based Anti-Sweating System for Bed Sore Prevention in a Clinical Environment - K. S. Jaichandar; Sampath Kumar; Chew kweeTiang; Siew Fong; Stewart Tai (Applied Bionics and Biomechanics)
Bed sores, a common problem among immobile patients occur as a result of continuous sweating due to increase in skin to bed surface temperature in patients lying on same posture for prolonged period. If left untreated, the skin can break open and become infected. Currently adopted methods for bed sores prevention include: use of two hourly flip chat for repositioning patient or use of air fluidized beds. However, the setbacks of these preventive measures include either use of costly equipment or wastage of human resources. This paper introduces an intelligent low cost FPGA based anti-sweating system for bed sores prevention in a clinical environment. The developed system consists of bed surface implanted temperature sensors interfaced with an FPGA chip for sensing the temperature change in patient’s skin to bed surface. Based on the temperature change, the FPGA chip select the - mode (heater/cooler) and speed of the fan module. Furthermore, an alarm module was implemented to alert the nurse to reposition the patient only if patient’s skin to bed surface temperature exceeds a predefined threshold thereby saving human resources. By integrating the whole system into a single FPGA chip, we were able to build a low cost compact system without sacrificing processing power and flexibility.